Screening of neuroprotective substances relevant to Alzheimer’s disease from seaweed species collected in Ninh Thuan and Khanh Hoa provinces, Vietnam - Thi Tam, Luu; Thi Minh Hien, Hoang; Thi Thom, Le; Cam Ha, Nguyen; Thi Hoai Thu, Ngo; Van Tru, Nguyen; Mai Duc, Tran; Thi Minh Hang, Nguyen; Hong, Dang Diem (Academia Journal of Biology, 2022)
Currently, nearly 36.5 million people live with Alzheimer’s disease worldwide, and acetylcholinesterase inhibition is considered the main treatment strategy against it. Seaweeds (or macroalgae) are a natural source of high-value bioactive compounds and have great potential in the production of health foods/foods, pharmaceuticals, cosmetics, animal feeds, biofertilizers, and biofuels. The most studied and applied seaweed species include red seaweed (Rhodophyta), green seaweed (Chlorophyta) and brown seaweed (Phaeophyta). This study aimed to evaluate the antioxidant and neuroprotective activities of extracts/substances isolated with solvents including ethanol 75o and 96o, water, n-hexane, ethyl acetate under normal and ultrasonic conditions (power 80W, frequency 4.7 kHz and for 1 hour) from 5 economically important seaweed species belonging to genera Caulerpa, Sargassum, Gracilaria, Ulva and Kappaphycus collected in Ninh Thuan and Khanh Hoa provinces, Vietnam. The results have shown that 05/30 extracts and substances (including SaE96S, SaH, SaHW, SaEA and fucosterol) isolated from five seaweed species exhibited high antioxidant activity through the free radical screening method using 2,2-diphenyl-1-picrylhydrazyl (DPPH) (with EC50 values < 5 mg/mL for extracts and EC50 value < 2 mM for substance) in comparison with positive control ascorbic acid (EC50 = 0.015 mg/mL); acetylcholinesterase inhibitory activity using acetylcholinesterase inhibitor screening KIT (with IC50 values of < 200 µg/mL for both extracts and substances), compared with positive control galantamine (with IC50 value of 52,8 µg/mL). The extracts/substances were able to protect the cell against cytotoxity in the C6 alzheimer’s disease cell model induced by amyloid beta-protein fragment (Aβ25-35). The results achieved from this research have proven that the extracts/substances isolated from seaweed species were a potential source of medicinal agents for the prevention and treatment of alzheimer’s disease.